Analyzing determinants of poverty in Central Java with Generalized Method of Moments - Elisandi, Dian Natalia Yesi; Dolfriandra Huruta, Andrian; Basukianto, Basukianto (Industrija, 2024)
The purpose of this study is to examine determinants of poverty in regencies/cities in Central Java. This study examined poverty, investment, savings, and infrastructure as the research variables by focusing on the vicious cycle of poverty. The data was obtained from the Central Bureau of Statistics in Central Java. The data was analyzed using the System-Generalized Method of Moments (SYS-GMM) model using a dynamic panel data model. The results show that both investment and infrastructure negatively and significantly impact poverty. However, saving has a positive and low significant impact on poverty. It was interesting to note that the disparity in savings ownership contributes to the high poverty level. These findings contribute to the government’s efforts to alleviate poverty in the regencies/cities in Central Java. Our findings also provide valuable insights into poverty dynamics in Indonesia.
Keywords: poverty, vicious cycle of poverty, central java, generalized method of moments